Odpowiedzi

2010-02-18T16:53:40+01:00
A). 4(y-3)-3(x+1) dla x=4, y=2
najpierw uproszczenie
4y-12-3x-3 = 4y -3x - 15
podstawiamy dane:
4*2 - 3*4 - 15 = 8 - 12 -15 = -19


b). 3(2b+1)-4(a-2) dla a=7, b=1
upraszczamy wyrażenie:
6b + 3 - 4a - 8 = 6b - 4a - 5
podstawiamy:
6*1 - 4*7 - 5 = 6 - 28 - 5 = -27

c). 9(x-7y)-(5y-2x)+20y dla x=0,5 y=0,3
9x - 63y - 5y + 2x + 20 y = 11x - 48 y
podst.
11*0,5 - 48 *0,3 = 5,5 - 14,4 = -8,9

d).(5x+7y)-8(y+1)+3(x-y) dla x=½ y=¼
5x+7y - 8y -8 +3x -3y = 8x - 4y - 8
podst.
8 * 1/2 - 4 * 1/4 - 8 = 4 - 1 - 8 = -5
5 3 5
2010-02-18T16:58:43+01:00
A). 4(y-3)-3(x+1) dla x=4, y=2
4(y-3)-3(x+1)=4y-12-3x-3=4*2-12-3*4=8-12-12=-16

b) 3(2b+1)-4(a-2) dla a=7, b=1
3(2b+1)-4(a-2)=6b+3-4a+8=6*1+3-4*7+8=6+3-28=-19

c) 9(x-7y)-(5y-2x)+20y dla x=0,5 y=0,3
9(x-7y)-(5y-2x)+20y= 9x-63y-5y+2x+20y=9*0,5-63*0,3-5*0,3+2*0,5+20*0,3=4,5-18,9-1,5+1+6=-9,9

d)(5x+7y)-8(y+1)+3(x-y) dla x=½ y=¼
(5x+7y)-8(y+1)+3(x-y)=5x+7y-8y-8+3x-3y=5*½-7*¼-8*¼+3*½-3*¼=2,½-7/4-2+1,5-3/4=-¼
2 3 2
2010-02-18T16:59:51+01:00
A).
4(y-3)-3(x+1) =
4y-12-3x-3 =
4y-3x-15 =
4*2-3*4-15 =
8-12-15 = -19

b).
3(2b+1)-4(a-2) =
6b+3-4a+8 =
6b-4a+11 =
6*1-4*7+11 =
6-28+11 = -11

c).
9(x-7y)-(5y-2x)+20y =
9x-63y-5y+2x+20y =
11x-48y =
11*0,5-48*0,3 =
5,5-14,4 = -8,9

d).
(5x+7y)-8(y+1)+3(x-y) =
5x+7y-8y-8+3x-3y =
8x-4y-8 =
8*1/2-4*1/4-8 =
4-1-8 = -5


3 3 3